2007
DOI: 10.1103/physrevlett.99.246102
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Surface States of Strained Cobalt Nanoislands on Cu(111)

Abstract: Low-temperature scanning tunneling spectroscopy over Co nanoislands on Cu(111) showed that the surface states of the islands vary with their size. Occupied states exhibit a sizeable downward energy shift as the island size decreases. The position of the occupied states also significantly changes across the islands. Atomic-scale simulations and ab inito calculations demonstrate that the driving force for the observed shift is related to size-dependent mesoscopic relaxations in the nanoislands.PACS numbers: 73… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 21 publications
(34 reference statements)
6
98
0
Order By: Relevance
“…The electronic properties show no significant difference for faulted and unfaulted Co islands. Only the dlike surface state shifts slightly in energy (< 50 mV) for differently oriented Co island as well as for different island sizes 60 . These small variations are specific for each Co island and, thus, necessitate that the spin-polarized measurements, namely for magnetically parallel and antiparallel configuration, must always be carried out on the same island and molecule, because otherwise the data are not comparable.…”
Section: A Co Islands On Cu(111)mentioning
confidence: 99%
“…The electronic properties show no significant difference for faulted and unfaulted Co islands. Only the dlike surface state shifts slightly in energy (< 50 mV) for differently oriented Co island as well as for different island sizes 60 . These small variations are specific for each Co island and, thus, necessitate that the spin-polarized measurements, namely for magnetically parallel and antiparallel configuration, must always be carried out on the same island and molecule, because otherwise the data are not comparable.…”
Section: A Co Islands On Cu(111)mentioning
confidence: 99%
“…It has been found that mesoscopic relaxations in a substrate can induce surprisingly fast diffusion of small clusters 43 , has a strong influence on the surface electronic structure of a nitrogen-covered metal substrate 56 and on the rates of chemical reactions on noble-metal surfaces 57 . The surface states over nanoscale islands are modified as the lateral size of an island changes, and this effect is also related to the size-dependent mesoscopic misfit 29,58 . Despite some indirect experimental evidence from stress 59,60 and reflection high-energy electron diffraction 61,62 experiments, the experimental verification of the concept of 'mesoscopic relaxations' came only recently using surface x-ray diffraction (SXRD) 47,48 by analyzing the static disorder of the Co atoms relative to the fourfold hollow sites of the Cu(001) substrate.…”
mentioning
confidence: 99%
“…In our setup, the counterelectrode can be conveniently chosen by posi- tioning a C 60 tip above nanoscale objects supported by Cu(111) or by changing the metal surface. Several counterelectrodes were inspected, either having a featureless electronic structure over the energy range of interest such as a Au atom on Cu(111) or the Cu(100) surface, either presenting a marked electronic structure such as a cobalt islands on Cu(111) [22], or a C 60 molecule on Cu(111).…”
mentioning
confidence: 99%